Molecular characteristics of serrated adenomas of the colorectum. - Sawyer, E; Cerar, A; Hanby, A; Gorman, P; Arends, M; Talbot, I; Tomlinson, I (2002)
BACKGROUND: Serrated adenomas (SAs) of the colorectum combine architectural features of hyperplastic polyps and cytological features of classical adenomas. Molecular studies comparing SAs and classical adenomas suggest that each may be a distinct entity; in particular, it has been proposed that microsatellite instability (MSI) distinguishes SAs from classical adenomas and that SAs and the colorectal cancers arising from them develop along a pathway driven by low level microsatellite instability (MSI-L). AIMS: To define the molecular characteristics of SAs of the colorectum. MATERIALS AND METHODS: We analysed 39 SAs from 27 patients, including eight SAs from patients with familial adenomatous polyposis (FAP). We screened these polyps for selected molecular changes, including loss of heterozygosity (LOH) close to APC (5q21) and CRAC1 (15q13-q22), MSI, and mutations of K-ras, APC, p53, and beta-catenin. Expression patterns of beta-catenin, p53, MLH1, MSH2, E-cadherin, and O(6)-methylguanine DNA methyltransferase (MGMT) were assessed by immunohistochemistry. Comparative genomic hybridisation was performed on several polyps. RESULTS: MSI was rare (<5% cases) and there was no loss of expression of mismatch repair proteins. Wnt pathway abnormalities (APC mutation/LOH, beta-catenin mutation/nuclear expression) occurred in 11 SAs, including 6/31 (19%) non-FAP tumours. CRAC1 LOH occurred in 23% of tumours. K-ras mutations and p53 mutations/overexpression were found in 15% and 8% of SAs, respectively. Loss of MGMT expression occurred in 18% of polyps and showed a borderline association with K-ras mutations. Aberrant E-cadherin expression was found in seven polyps. Comparative genomic hybridisation detected no gains or deletions of chromosomal material. CONCLUSIONS: The serrated pathway of colorectal tumorigenesis appears to be heterogeneous. In common with classical adenomas, some SAs develop along pathways involving changes in APC/beta-catenin. SAs rarely show MSI or any evidence of chromosomal-scale genetic instability. K-ras mutations may however be less common in SAs than in classical adenomas. Some SAs may harbour changes in the CRAC1 gene. Changes in known genes do not account for the growth of the majority of SAs.